Interpolation formula between very low and intermediate-to-high damping Kramers escape rates for single-domain ferromagnetic particles - COFFEY, WILLIAM THOMAS (American Physical Society, 2001)
It is shown that the Mel?nikov-Meshkov formalism for bridging the very low damping (VLD) and intermediate-to-high damping (IHD) Kramers escape rates as a function of the dissipation parameter for mechanical particles may be extended to the rotational Brownian motion of magnetic dipole moments of single-domain ferromagnetic particles in nonaxially symmetric potentials of the magnetocrystalline anisotropy so that both regimes of damping occur. The procedure is illustrated by considering the particular nonaxially symmetric problem of superparamagnetic particles possessing uniaxial anisotropy subject to an external uniform field applied at an angle to the easy axis of magnetization. Here the Mel?nikov-Meshkov treatment is found to be in good agreement with an exact calculation of the smallest eigenvalue of Brown?s Fokker-Planck equation, provided the external field is large enough to ensure significant departure from axial symmetry, so that the VLD and IHD formulas for escape rates of magnetic dipoles for nonaxially symmetric potentials are valid.
PUBLISHED
Keywords: Electronic & Electrical Engineering